Influence of Bank Type on the Relationship Between Corporate Governance and Market Performance: Insights from Emerging Countries - Sheikh Khurram Abid; Muhammad Akram Naseem; Muhammad Zain ul Abidin (Journal of Accounting and Finance in Emerging Economies)
Purpose: The market performance of banks is highly impacted by corporate governance and type of bank. This study aims to empirically examine the influential impact of bank type on the relationship between corporate governance and bank’s market performance.